Efektivitas Pengaturan Parkir Liar Terkait Peraturan Daerah Kota Denpasar Nomor 13 Tahun 2016 Tentang Penyelenggaraan Perhubungan - Sulistyawati, Ni Putu Yunika; Kusumawardhani, Sang Ayu Made Ary; Novita Yogan Dewi, Ida Ayu (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Violations occur because motorists do not obey road signs and markings, which results in congestion and is more at risk of leading to an accident. The government, in this case the city government of Denpasar, has issued Regional Regulation for the City of Denpasar Number 13 of 2016 concerning the implementation of transportation. The research method is empirical legal research. From the results of research on the Effectiveness of Illegal Parking Regulations Related to the Regional Regulation of the City of Denpasar Number 13 of 2016 concerning the Implementation of Transportation, the Denpasar City Transportation Agency takes action in accordance with Article 142 paragraph (4) to take action against violations against vehicle owners and / or drivers as referred to in paragraph (3) done by: affixing stickers; locking and / or fixing the chain on the wheels of a motorized vehicle, tire grinding (removing the valve); and towing with this rule reduces illegal offenses by the side of the road, so that it can be said to be effective.